A Comprehensive Survey on Sentiment Analysis and Opinion Mining - Bhuvaneswari, R; Ravichandran, S (International Journal of Computer Sciences and Engineering, 2025)
The colossal volume of data available on the internet media and the evolution of internet and social media, the internet user articulates their opinion, suggestion and views on the web. The comprehensive study of user opinion is quite imperative in the decision making processes. Unearthing the useful content from these opinion sources is a tedious and cumbersome task and this formed a new sector of research field named opinion mining and sentiment analysis. Opinion mining and sentiment analysis automatically extract and classify the user’s opinion clearly. This paper focuses on the review of Opinion mining about a particular topic written in a natural language and classifies them as positive, negative or neutral based on the humans emotions involved in it